1999
DOI: 10.1126/science.285.5429.901
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the S. cerevisiae Genome by Gene Deletion and Parallel Analysis

Abstract: The functions of many open reading frames (ORFs) identified in genome-sequencing projects are unknown. New, whole-genome approaches are required to systematically determine their function. A total of 6925 Saccharomyces cerevisiae strains were constructed, by a high-throughput strategy, each with a precise deletion of one of 2026 ORFs (more than one-third of the ORFs in the genome). Of the deleted ORFs, 17 percent were essential for viability in rich medium. The phenotypes of more than 500 deletion strains were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
2,914
5
19

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 3,786 publications
(2,966 citation statements)
references
References 36 publications
28
2,914
5
19
Order By: Relevance
“…This simulated tolerance against random mutation is in agreement with systematic mutagenesis studies, which identified a striking capacity of yeast to tolerate the deletion of a substantial number of individual proteins from its proteome 9,10 . Yet, if indeed this is due to a topological component to error tolerance, on average less connected proteins should prove less essential than highly connected ones.…”
supporting
confidence: 85%
“…This simulated tolerance against random mutation is in agreement with systematic mutagenesis studies, which identified a striking capacity of yeast to tolerate the deletion of a substantial number of individual proteins from its proteome 9,10 . Yet, if indeed this is due to a topological component to error tolerance, on average less connected proteins should prove less essential than highly connected ones.…”
supporting
confidence: 85%
“…Our vectors can integrate into commonly used auxotrophic yeast strains, including the designer deletion strains (Brachmann et al, 1998), making them compatible with the diverse strain collections (Winzeler et al, 1999;Huh et al, 2003;Ghaemmaghami et al, 2003;Mnaimneh et al, 2004). Efficient integration into the various alleles (carrying point mutations, insertions, partial or complete deletions) is facilitated by using marker genes on the plasmids without any overlap with the host genome (Wach et al, 1997;Goldstein et al, 1999;Gueldener et al, 2002 For the extrachromosomal maintenance of genes at low or high copy number, the series contains centromeric and episomal shuttle vectors, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…1). The first was generated by SGA, a large-scale screen 10 crossing 132 yeast gene deletion strains versus each of the ~4,700 available deletion strains 22 and resulting in 2,012 observed synthetic-lethal interactions and 2,113 synthetic-sick interactions. The second data source consisted of an additional 687 synthetic-lethal interactions culled from the literature and catalogued at the Munich Information Center for Protein Sequences (MIPS) 23 .…”
Section: Construction Of Genetic and Physical Networkmentioning
confidence: 99%